Pengaruh Kemandirian, Efisiensi Keuangan Daerah, dan Dana Transfer Terhadap Financial Sustainability pada Pemerintah Provinsi di Sumatera - Mardiana Ayu Lestari; Kartika Rachma Sari; Sukmini Hartati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted to examine the factors affecting financial sustainability in provincial governments in Sumatra. The study was measured using data from the Local Government Financial Reports (LKPD) for the period 2019-2023. This study is a quantitative study. The population used in this study consisted of 10 provinces in Sumatra. Sampling was conducted using saturated sampling techniques. Data collection techniques used documentation. Data sources utilized secondary data. Data analysis methods employed panel data multiple regression analysis. The results of this study can be concluded that, partially, the variables of Financial Independence, Regional Financial Efficiency, and Transfer Funds have a significant impact on financial sustainability. Additionally, simultaneously, Financial Independence, Regional Financial Efficiency, and Transfer Funds have a significant impact on financial sustainability in provincial governments in Sumatra.